2011
DOI: 10.1111/j.1348-0421.2010.00294.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of 3′ termini of human cytomegalovirus UL138-UL145 transcripts in a clinical strain

Abstract: The functions of some proteins encoded by human cytomegalovirus (HCMV) UL/b genes have been studied; however, systematic analysis of the transcripts for this region is still insufficient. The results of both rapid amplification of cDNA ends (RACE) and cDNA library screening in this study proved that 3 termini of all transcripts in the UL138-UL145 region were located approximately 20 bp downstream from each potential poly (A) signal, which were at the positions of nucleotides 7184, 9954 and 12848 in the UL/b se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The relative conservation of UL145 sequences being retained under selection pressure suggests that it might be essential for virus survival and replication in vivo. Qi et al [2011] have identified the transcripts of the UL138-UL145 region as two large families of polycistronic transcripts, with the UL145 gene representing one component of the second family. He et al [2011] have confirmed that UL144 and UL145 are expressed as a polycistron.…”
Section: Discussionmentioning
confidence: 99%
“…The relative conservation of UL145 sequences being retained under selection pressure suggests that it might be essential for virus survival and replication in vivo. Qi et al [2011] have identified the transcripts of the UL138-UL145 region as two large families of polycistronic transcripts, with the UL145 gene representing one component of the second family. He et al [2011] have confirmed that UL144 and UL145 are expressed as a polycistron.…”
Section: Discussionmentioning
confidence: 99%
“…A pair of specific primers for the UL21.5 gene region (R-s3 and 5'R3) (Table I and Fig. 1) were designed and used to screen UL21.5 genespecific clones from the cDNA library by graded polymerase chain reaction (PCR) as described in previous studies (21,22). The PCR reaction conditions were as follows: 95˚C for 5 min, 30 cycles of 95˚C for 45 sec, 56˚C for 45 sec and 72˚C for 30 sec, followed by a final elongation at 72˚C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…To select specific cDNA clones from the cDNA library by PCR, a graded PCR was set up as previously described [19,20]. Five thousand cDNA clones were screened by graded PCR using several pairs of primers (Table 1, Figure 1).…”
Section: Methodsmentioning
confidence: 99%